If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4(x + -8) = 3(2x + 12) Reorder the terms: 2x + 4(-8 + x) = 3(2x + 12) 2x + (-8 * 4 + x * 4) = 3(2x + 12) 2x + (-32 + 4x) = 3(2x + 12) Reorder the terms: -32 + 2x + 4x = 3(2x + 12) Combine like terms: 2x + 4x = 6x -32 + 6x = 3(2x + 12) Reorder the terms: -32 + 6x = 3(12 + 2x) -32 + 6x = (12 * 3 + 2x * 3) -32 + 6x = (36 + 6x) Add '-6x' to each side of the equation. -32 + 6x + -6x = 36 + 6x + -6x Combine like terms: 6x + -6x = 0 -32 + 0 = 36 + 6x + -6x -32 = 36 + 6x + -6x Combine like terms: 6x + -6x = 0 -32 = 36 + 0 -32 = 36 Solving -32 = 36 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (2m+9)(m-7)=0 | | =x^2+40x-100 | | -2x-6-3x=1 | | 0.67x-3.5=2.25 | | =2x^2+8x+8 | | x=2+0.5y | | =2x^2 | | 2k+4=10 | | =x^2-100x+2500 | | x=-4-9(-1) | | 3x+7-9x=2(8x-5) | | v^2+5v-9= | | 14x^2+29x-15=0 | | 4x^2-108=5x^2+21x | | -12-27y+12y=3 | | 6.5x-2.58=3.9-4.3x | | 0.25x-0.875=0.625 | | 5xy+1=4y-9x | | -8x=17 | | 6a^2+54a+48=0 | | 3x*5y*2z=5 | | 21x-5=9+14x | | 25c^2-9=0 | | 3x*5y*2z=0 | | ab+ax=c-ax | | 4u^2+9u+5= | | (35x-16)=31x | | 0.67x+0.3=2.4 | | B-4[B-3(5-B)]= | | t(7t+1)= | | 100w^2-9=0 | | 6x+3=3x-21 |